2008
DOI: 10.1103/physrevd.77.034505
|View full text |Cite
|
Sign up to set email alerts
|

Diquark effects in light baryon correlators from lattice QCD

Abstract: We study the role of diquarks in light baryons through point to point baryon correlators. We contrast results from quenched simulations with ones with two flavors of dynamical overlap fermions. The scalar, pseudoscalar and axial vector diquarks are combined with light quarks to form color singlets. The quenched simulation shows large zero mode effects in correlators containing the scalar and pseudoscalar diquark. The two scalar diquarks created by γ5 and γ0γ5 lead to different behavior in baryon correlators, s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 29 publications
(48 reference statements)
0
24
0
Order By: Relevance
“…Earlier lattice studies that have paired two light quarks with a static quark [18,19] have shown a large diquark (Oð1Þ fm) can form inside of a baryon, though with limited effect on the structure of the particle. More recently, light quarks have been paired with various diquark correlators [20] which suggest that diquarks are not a significant factor in light baryons. To the best of our knowledge, this is the first time that such a diquark configuration has been shown in a baryon composed of three light quarks.…”
Section: Zero-field Resultsmentioning
confidence: 99%
“…Earlier lattice studies that have paired two light quarks with a static quark [18,19] have shown a large diquark (Oð1Þ fm) can form inside of a baryon, though with limited effect on the structure of the particle. More recently, light quarks have been paired with various diquark correlators [20] which suggest that diquarks are not a significant factor in light baryons. To the best of our knowledge, this is the first time that such a diquark configuration has been shown in a baryon composed of three light quarks.…”
Section: Zero-field Resultsmentioning
confidence: 99%
“…Many articles have been written on this subject since its introduction (for a review, see Ref. [23]) and more recently the diquark concept has been used in several studies, ranging from one-gluon exchange to lattice QCD calculations [24][25][26][27][28][29][30][31][32][33][34]. Important phenomenological indications for diquark-like correlations [28][29][30]35,36] and for diquark confinement [37] have also been provided.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, many papers have been written on this topic (for a review see Ref. [16]) and, more recently, the diquark concept has been applied to various calculations [17][18][19][20][21][22][23][24][25][26][28][29][30][31][32][33][34][35][36][37]. Important phenomenological indications for diquark-like correlations have been collected [17,19,38,39] and indications for diquark confinement have also been provided [40].…”
Section: Introductionmentioning
confidence: 99%